Solvent-free halloysite nanotubes nanofluids based polyacrylonitrile fibrous membranes for protective and breathable textiles. (August 2022) - Lv, Yekun; Sun, Xiang; Yan, Song; Xiong, Siwei; Wang, Luoxin; Wang, Hua; Yang, Shiwen; Yin, Xianze
Abstract: The existing strategies for effective particulate matter (PM) removal rely on high-performance electrostatically spun nanofiber membranes, as PM pollution has become a serious public health concern. Incorporation of nanoparticles is one of the common means to prepare multifunctional nanofiber membranes with high filtration efficiency, but the dispersion of nanoparticles in the fibrous membranes remains a major challenge. Here, we demonstrated multifunctional nanofiber membranes by preparing halloysite nanotubes nanofluids (HNTfs) and then introducing them into conventional electrospun polyacrylonitrile fibrous membranes. The EDS-mapping results showed that HNTfs were uniformly dispersed in the fibrous membranes. The PAN/HNTfs fibrous membranes obtained had a high removal rate of 99.5% for small-sized aerosols which the diameter was 0.3 μm. More importantly, compared with the pure PAN nanofiber membranes, the PAN/HNTfs fibrous membranes changed from hydrophobic to superhydrophilic. At the same time, the samples exhibited good moisture permeability and air permeability after adding HNTfs. Moreover, the PAN/HNTfs fibrous membranes had an enhancement of 125.0% for thermal conductivity compared with the pure PAN at 20 wt% HNTfs loading, thus improved the heat dissipation. Therefore, it can be expected that the PAN/HNTfs fibrous membranes would be widely used in wearable protective fabrics as a high performance protective material. Graphical abstract: Image 1 Highlights: The HNTfs were designed and rooted into PAN fibrous membranes via electrospinning. The fibrous membranes with multiple functions were successfully prepared. The HNTfs enhances the wearability of the fibrous membranes. The fibrous membranes had excellent removal efficiency for small-sized aerosols.